Prioritizing SCADA Integration at Keypoints Using Fuzzy AHP and TOPSIS Methods: A Case Study in PLN UP2D Makassar - Arief Nurhidayanto; Ratna Sari Dewi (Jurnal Indonesia Sosial Teknologi, 2024)
PLN UP2D Makassar regulates the 20 kV electrical distribution network in South Sulawesi, Southeast Sulawesi, and West Sulawesi. PLN UP2D Makassar holds a management contract, which is SCADA integration. Based on the Network Database Book, in 2023, there were 128 key points (LBS and reclosers) that were not yet integrated with SCADA or not online with the Master SCADA. The current issue identified in making decisions on SCADA integration to critical points in PLN UP2D Makassar is using the crucial point ratio Value per PLN UP3 criteria. The weakness of this method is that SCADA integration at key points does not consider the benefits and impacts of SCADA integration, such as the improvement of SAIDI and ENS. This study aims to create guidelines for decision-making on SCADA integration at critical points. This research involves five experts in PLN UP2D Makassar. A total of 6 criteria were established and processed using the Fuzzy AHP TOPSIS method to rank the 128 key points that will be integrated with SCADA. The Fuzzy AHP TOPSIS calculation results have been validated with a consistency ratio of -0.008 (consistent) and sensitivity analysis (10% increase/decrease in criteria weight). This means that the proposed six criteria can be used to rank alternative vital points that will be integrated with SCADA.